PENGARUH FIRM SIZE, SALES GROWTH DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE - Sari, Melda; Setyawati, Wiwit (Jurnal Nusa Akuntansi, 2025)
This research aims to analyze the influence of Firm Size, Sales Growth, Transfer Pricing on Tax Avoidance. This research was conducted on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) during the period2019 to 2023, consisting of 90 data.The sample was taken using a purposive sampling technique, resulting in a sample of 18 companies with observations for 5 (five) years. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The data analysis method uses panel data regression analysis. .The test tool used is the EViews 12 program. Based on the results of hypothesis testing, it is shown that Firm Size, Sales Growth, Transfer Pricing simultaneously have a significant influence on Tax Avoidance. .partially, only Firm Size has a significant influence on Tax Avoidance, while Sales Growth and Transfer Pricing do not have a significant influence on Tax Avoidance.